Activity of Antioxidant Enzymes in Wistar and SHR Rats on a High-Calorie Diet - Svetlana V. Notova; Olga V. Marshinskaia; Tatiana V. Kazakova (Northern (Arctic) Federal University, 2024)
Over the last decades, the dietary pattern of the population has undergone changes, including a significant increase in the consumption of high-calorie food. The purpose of this study was to investigate the activity of antioxidant enzymes in rats with and without genetic predisposition to cardiovascular disease eating a high-calorie diet. Materials and мethods. Wistar (n = 30) and SHR rats (n = 30; predisposed to cardiovascular disease) were used. Animals of both strains were subdivided into two groups: control (basic diet) and experimental (high-calorie diet). Parameters of carbohydrate and lipid metabolism were determined using a biochemistry analyser; haematological analysis was performed in order to establish the type of nonspecific adaptive response of the body. The state of the antioxidant system was evaluated using the animals' blood serum and liver homogenate by determining catalase, superoxide dismutase and glutathione peroxidase activity. Results. High-calorie diet led to excessive body weight, changes in lipid profile, impaired glucose tolerance and inadequate adaptive response of the functional systems (manifested in the strain on the adaptive mechanisms and maladaptation) as well as to depletion of antioxidant enzymes in rats of both experimental groups. The parameters of animals with and without genetic predisposition to cardiovascular disease were found to be virtually identical. Despite the fact that genetic factors contribute significantly to the development of metabolic pathologies, the results obtained in the group of Wistar rats confirm that excessive caloric intake is one of the major causes of metabolic disorders.